PENGARUH LATIHAN SNAKE JUMP AGILITY LADDER DRILLTERHADAP KELINCAHAN PADA SSBU-15 PTPN V - Purwandi, Wira; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The problem in the research that the agilityPTPN V SSB U-15 is still lacking, this from the various test and tournament and tesis one of the causes of the defeat.This type of research is a kind of research experiments to see the effects of this form of exercise that is given. The purpose of this research was to observe the effect of practice snake jump